Fostering Pre-Service Primary Teachers’ Capacity to Employ an Interactive Learning Tool - Nurgul Alpysbayeva; Gulnar Zholtaeva; Gulnar Tazhinova; Gulnara Syrlybayeva; Raushan Assylova (Qubahan Academic Journal)
This investigation examined the efficacy of a researcher-designed course intended to bolster primary student-teachers’ capabilities in leveraging interactive learning through a smart voice device Alisa, the ubiquitous physical device popular among Russian-speaking demographics. An embedded mixed design was adopted, integrating qualitative explorations within a predominantly quantitative framework. Over ten weeks, 37 pre-service elementary teachers engaged in a program structured around interactive learning principles, Alisa classroom implementation, and microteaching sessions. Eventually, the teachers-in-training demonstrated notable advancement in crafting interactive, technology-enriched lesson plans. Furthermore, there was a step up in their teaching self-efficacy, with participants expressing increased confidence in harnessing the smart speaker. Semi-structured interviews revealed three primary deterrents encountered during the intervention: troubleshooting technical expectancies, puzzling over effectively embodying Alisa into relevant activities, and the considerable time investment required for planning interactive lessons with the voice-controlled assistants. By evaluating the potential pros and cons of integrating smart speakers into education, this study sets the stage for future inquiries. The findings foreground the potential of incorporating natural conversation assistants into primary teacher education programs while also pointing to the necessity of addressing the hurdles identified herein.